FACTORS INFLUENCING INTERACTION IN AN ONLINE ENGLISH COURSE IN VIETNAM - Thach, Pham Ngoc (VNU Journal of Foreign Studies, 2020)
This study examines the factors that influenced learners’ online interaction in an online English learning course offered at a Vietnamese university using mixed methods approach and principal component analysis. It explores which factors would have impact on learners’ interaction with the content, peers and instructors in the course as well as the level of importance for each factor. The findings of the study indicated that factors related to the online course were its content and flexible delivery while those concerning the learners were their internet self-efficacy as well as their perceived usefulness of interaction processes. The factors related to the instructors included timeliness and usefulness of feedback and their online presence. In addition, in Vietnamese context, the cultural factors such as being passive, fear of asking questions to instructors also influenced learners’ online interaction.